Sie sind auf Seite 1von 3

# AIEEEportal.

com

Binomial Theorem
1. 2. 3. 4. 5. If n is a positive integer then ( x + a)n = n C 0 x n + nC1x n 1a + n C 2 x n 2 a 2 + ... + nCr x n r a r + ...... + nCna n . The expansion of ( x + a)n contains (n + 1) terms. In the expansion, the sum of the powers of x and a in each term is equal to n. In the expansion, the coefficients n C 0 , nC1, n C 2 ,...,n Cn are called binomial coefficients and these are simply denoted by C0 , C1, C 2 ,..., Cn . In the expansion, (r + 1)th term is called the general term. It is denoted by Tr +1 . Thus Tr +1 = n Cr x n r ar .
( x + a )n =

6. 7. 8. 9.

r =0 n n

Cr x n r a r .

( x a )n =

r =0
n

Cr x n r ( a)r =

(1)
r =0

n n

(1 + x )n =

r =0

## Middle term(s) in the expansion of (x + a)n :

n i) If n is even then + 1 th term is the middle term. 2

## 10. Numerically greatest term in the expansion of (1 + x)n : i) If

(n + 1) | x | = | x | +1

p, a positive integer then pth and (p+1)th terms are the numerically greatest terms

## in the expansion of (1 + x)n. ii) If

(n + 1) | x | = | x | +1

p+F where p is a positive integer and 0 < F < 1 then (p+1)th term is the

numerically greatest term in the expansion of (1+x)n. 11. If Cr denotes n Cr then i) C0 + C1 + C 2 + ... + Cn = 2n ii) C0 + C 2 + C 4 + ... = C1 + C3 + C 5 + ... = 2n 1 12. i)

r =0

Cr = 2n

ii)

(1)
r =0

r n

Cr = 0

## 13. aC0 + (a + d)C1 + (a + 2d)C2 ++ (a + nd)Cn = (2a + nd) 2n1. 14.

C1 + 2 C 2 x + 3 C 3 x 2 + ... + n C n x n 1 = n(1 + x) n 1

Binomial Theorem
15. i) C1 + 2 C 2 + 3 C3 + ... + n Cn = n 2n 1 ii) C1 2 C 2 + 3 C 3 ...... = 0 16. i)

r.
r =0

Cr = n.2n 1

ii)

(1) r.
r r =0

Cr = 0

17.
18. 19.

C0 +

C C1 C (1 + x) n +1 1 x + 2 x 2 + .... + n x n = . n +1 2 3 (n + 1) x
2n

C 0 C r + C1C r +1 + C 2 C r + 2 + ..... + C nr C n =
2 2 2 C0 + C1 + C2 2 + ... + C n =

C n r

(2n)! . (n r )! (n + r )!

(2n)! (n! ) 2

20. Binomial Theorem for rational index : If n is a rational number and |x| < 1 then 1+nx +
n(n + 1) 2 n(n 1)(n 2) 3 x + .... = (1 + x )n . x + 3! 2!

21. If |x| < 1 then i) (1 + x)1 = 1 x + x 2 x 3 + ... + ( 1)r x r + ... ii) (1 x)1 = 1 + x + x 2 + x 3 + ... + x r + ... iii) (1+x)2= 1 2x + 3 x 2 4 x 3 + ... + ( 1)r (r + 1)x r + ... iv) (1 x)2 = 1 + 2x + 3x 2 + 4x 3 + ... + (r + 1)x r + ... v) (1 + x ) n = 1 nx +
n(n 1) 2 n(n 1)(n 2) 3 x + ... x 3! 2! n(n + 1) 2 n(n + 1)(n + 2) 3 x + ... x + 3! 2!
p(p + q) x + 2! p
2

vi) (1 x ) n = 1 + nx +
p

vii) (1 x ) q = 1 + p +

x p

## p(p + q)(p + 2q) x p + ... 3!

22. If |x| < 1 and n is a positive integer, then i) (1 x ) n = 1 + nC1x + (n +1)C 2 x 2 + (n + 2)C 3 x 3 + ... ii) (1 + x ) n = 1 n C1x + (n +1)C 2 x 2 (n + 2)C3 x 3 + ...
b np m p 23. Coefficient of x m in the expansion of . ax + q is the coefficient of Tr +1 where r = x
n

p+q

## 25. In the expansion ( x + a)n ,

Tr +1 n r + 1 a . = Tr r x

## 26. The general term in the expansion of ( x1 + x 2 + ... + x p )n is

n1 + n 2 + ... + np = n.

## n! n x n1 x n2 ...x np where n1! n 2 !...np ! 1 2

Binomial Theorem
27. i) The coefficient of x n 1 in the expansion of (x 1)(x 2) (x n) is n(n+1)/2. ii) The coefficient of x n 1 in the expansion of (x + 1)(x + 2) (x + n) is n(n+1)/2. ii) If the coefficients of x r , x r +1 in the expansion of (a + x/b)n are equal then n = (r+1)(ab+1) 1. 29. i) If the coefficients of rth, (r+1)th, (r+2)th terms of (1 + x)n are in A.P. then n2 (4r+1)n + 4r2=2. ii) If the coefficients of x r 1, x r , x r +1 are in A.P. then (n 2r)2 = n + 2. 30. If (a + b )n = I + F were I, n are positive integers, 0 < F < 1, a2 b = 1, then i) I is an odd positive integer ii) (I + F)( I F) = 1. 31. i) The number of terms in the expansion of ( x + a)n + ( x a)n is (n+2)/2 if n is even, (n+1)/2 if n is odd. ii) The number of terms in the expansion of ( x + a)n ( x a)n is n/2 if n is even, (n+1)/2 if n is odd. 32. Sum of the coefficients of (ax + by)n is (a + b)n. 33. If f(x) = (a0 + a1x + a2x2 ++ amxm)n then i) Sum of the coefficients = f(1). ii) Sum of the coefficients of even powers of x is iii) Sum of the coefficients of odd powers of x is 34. 35. 36.
2 = a.C 0 + (a + d).C1 + (a + 2d).C 2 + ... + (a + nd).C n 2 2 2

28. i) If the coefficients of pth, qth terms in the expansion of (1 + x)n are equal then p+q = n+2.

f (1) + f ( 1) . 2

f (1) f ( 1) . 2

1 (2a + nd). 2n Cn . 2

C 0 Cr + C1Cr + 1 + C 2 Cr + 2 + ... + Cn r Cn = 2n Cn r .
m

C 0 n Cr + m C1 n Cr 1 + m C 2 n Cr 2 + ... + m Cr n C 0 =

(m + n)

Cr .

AIEEEportal.com